TOTAL QUALITY MANAGEMENT (TQM) IMPLEMENTATION AND ORGANISATIONAL PERFORMANCE: A STUDY OF THE TELECOMMUNICATION INDUSTRY IN BAYELSA STATE OF NIGERIA - Laguo Livingstone Gilbert; Felix Oluwatayo Oloda (American Journals, 2023)
Purpose - The purpose of this paper is to determine the factors of total quality management (TQM) and to measure their influence on the performance of selected telecommunication companies in Bayelsa State.Design/methodology/approach - Data was collected using a self-administered questionnaire which was distributed to 200 personnel in telecommunication companies in Yenagoa, the capital city of Bayelsa State. Out the 200 questionnaires, a total of 188 questionnaires were returned.Findings - The findings from the study reveal that TQM plays critical role in the improvement of organisational performance. However, the value of top management support, quality data reporting, and process flow management are better appreciated when implementing TQM in the telecommunication organisations under study.Research limitations/implications - a quantitative technique was adopted in the study, the sample is restricted to organisations selected. The data were collected from both top and middle managers in the selected organisations.Originality/value - This study offers insight into practical and reasonable approaches of TQM variables to increase performance in the Nigerian telecommunication sector.Paper type research paper
Keywords: Total quality management, organisational performance, Nigeria telecommunication sector